Ultrastructural and Molecular Analyses Reveal Enhanced Nucleolar Activity in Medicago truncatula Cells Overexpressing the MtTdp2α Gene - Macovei, Anca; Faè, Matteo; Biggiogera, Marco; de Sousa Araújo, Susana; Carbonera, Daniela; Balestrazzi, Alma (Frontiers in Plant Science, 2018)
The role of tyrosyl-DNA phosphodiesterase 2 (Tdp2) involved in the repair of 5’-end-blocking DNA lesions is still poorly explored in plants. To gain novel insights, Medicago truncatula suspension cultures overexpressing the MtTdp2alpha gene (Tdp2alpha-13C and Tdp2alpha-28 lines, respectively) and a control (CTRL) line carrying the empty vector were investigated. Transmission electron microscopy (TEM) revealed enlarged nucleoli (up to 44% expansion of the area, compared to CTRL), the presence of nucleolar vacuoles, increased frequency of multinucleolate cells (up to 4.3-fold compared to CTRL) and reduced number of ring-shaped nucleoli in Tdp2alpha-13C and Tdp2alpha-28 lines. Ultrastructural data suggesting for enhanced nucleolar activity in MtTdp2alpha-overexpressing lines were integrated with results from bromouridine incorporation. The latter revealed an increase of labeled transcripts in both Tdp2alpha-13C and Tdp2alpha-28 cells, within the nucleolus and in the extra-nucleolar region. MtTdp2alpha-overexpressing cells showed tolerance to etoposide, a selective inhibitor of DNA topoisomerase II, as evidenced by DNA diffusion assay. TEM analysis revealed etoposide-induced rearrangements within the nucleolus, resembling the nucleolar caps observed in animal cells under transcription impairment. Based on these findings it is evident that MtTdp2alpha-overexpression enhances nucleolar activity in plant cells.